Analysis of the Strength of a Deed Made by a Notary Against the Concept of Cyber Notary - Al Hadid, Andi Pangerang; Nur’aini, Tiya; Christy, Florentina; Tjempaka, Tjempaka (Sultan Agung Notary Law Review, 2024)
Technological advances are increasingly developing every year, bringing impacts to all aspects, especially in the field of notary. One of them is the concept of Cyber Notary which uses electronic media in every act, while the field of notary has not regulated this, therefore this condition requires further research. The problem taken in this study is whether the deed remains an authentic deed if using the Cyber Notary concept based on the Notary Law and the Electronic Information and Technology Law and solutions to deal with digital developments for Notaries when making deeds. This study uses descriptive Normative Law Research. The results of this study indicate that according to Law Number 2 of 2014 concerning the Notary, basically the concept cannot be applied because based on Article 16 paragraph 1 letter m it stipulates that after the deed is read in front of the parties, witnesses and Notary, the deed is signed at that time, therefore in this case it is necessary to have harmonization between the Notary Law and the Law on Information and Electronic Transactions.